Relationship Between Total Suspended Solid (TSS) and Phytoplankton Abundance in the Waters of Rupat Strait, Riau Province - Alqoriffah Hasanah; Irvina Nurrachmi; Syafruddin Nasution (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
This study was conducted in March 2023 in the waters of the Rupat Strait, Riau Province. This study aimed to determine the total suspended solid (TSS) concentration, the type and abundance of phytoplankton, and the relationship between TSS concentration and phytoplankton in the Rupat Strait waters. The method used was a survey method; the location of the study was determined by purposive sampling; there were 4 sampling stations consisting of 3 sampling points. The results showed that the highest average TSS was at Station 4 (98.33 mg/L), and the lowest was at Station 1 (85 mg/L). There were 14 types of phytoplankton found, namely Nitzschia sp, Synedra ulna, Isthmia obliquita, Rhabdonema adriticum, Grammatophora sp, Guinardia striata, Rhizosolenia alata, Cyclotella atomus, Oscillatoria sp, Lyngbya sp, Tolypothrix sp, Pleurotaenium sp, Closterium sp, Gonatozygon sp with the most dominant species being Isthmia obliquata, Synedra ulna, Grammatophora sp. The highest abundance was in the Darul Aman area (5004.207 ind/L), and the lowest was in the Bandar Bakau area (2573.592 ind/l). The relationship between TSS and phytoplankton abundance shows a strong and negative relationship, meaning that the higher the TSS, the lower the abundance of phytoplankton in the waters of Rupat Strait.